The Psychological and Economic Impact of Residents on the Closure of Bong Suwung Localization in Yogyakarta City - Mujiyanto Mujiyanto; Sugiyanto Sugiyanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Economic development in Indonesia aims to improve people's living standards and welfare, but challenges such as high poverty rates are still a significant problem, especially in the Special Region of Yogyakarta (DIY). This study aims to analyze the economic impact of the closure of the localization of Bong Suwung, which is one of the centers of prostitution in Yogyakarta. Approach to descriptive qualitative research. Data is collected by observation, interview, and documentation techniques, primary and secondary data are integrated in the context of analysis, informance is determined by propulsive sampling. The results of the study show that the closure of localization has a negative impact on people's incomes, including traders, parking attendants, and commercial sex workers (PSK). Many traders lost customers and income, while prostitutes were forced to look for new locations to operate. On the other hand, the closure affects the psychological condition of children from affected families, who have difficulty in continuing their education. This research highlights the importance of a more comprehensive approach in dealing with social and economic problems, as well as the need for support for affected communities to adapt and find alternative sources of livelihood.